2019
DOI: 10.3389/fimmu.2019.00923
|View full text |Cite
|
Sign up to set email alerts
|

Priming With Recombinant BCG Expressing Novel HIV-1 Conserved Mosaic Immunogens and Boosting With Recombinant ChAdOx1 Is Safe, Stable, and Elicits HIV-1-Specific T-Cell Responses in BALB/c Mice

Abstract: BCG is currently the only licensed vaccine against tuberculosis (TB) and confers protection against meningitis and miliary tuberculosis in infants, although pulmonary disease protection in adults is inconsistent. Recently, promising HIV-1 immunogens were developed, such as the T-cell immunogens “tHIVconsvX,” designed using functionally conserved protein regions across group M strains, with mosaic immunogens to improve HIV-1 variant match and response breadth. In this study, we constructed an integrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…When delivered using DNA and MVA vectors, it has been shown to be capable of inducing broadly and evenly distributed immune responses of high magnitude in mice and monkeys [7]. We have previously demonstrated the in vitro and in vivo stability of the integrative plasmid p2auxo.int for expressing HIV-1 immunogens in BCG [33,43]. Here, we produced the BCG.HTI 2auxo.int vaccine candidates under Good Laboratory Practice compatible conditions, and characterized them genotypically and phenotypically, confirming the presence of the HTI gene and protein in the lysates of working vaccine stocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When delivered using DNA and MVA vectors, it has been shown to be capable of inducing broadly and evenly distributed immune responses of high magnitude in mice and monkeys [7]. We have previously demonstrated the in vitro and in vivo stability of the integrative plasmid p2auxo.int for expressing HIV-1 immunogens in BCG [33,43]. Here, we produced the BCG.HTI 2auxo.int vaccine candidates under Good Laboratory Practice compatible conditions, and characterized them genotypically and phenotypically, confirming the presence of the HTI gene and protein in the lysates of working vaccine stocks.…”
Section: Discussionmentioning
confidence: 99%
“…(D) PCR detection of the GlyA gene in the BCG.HTI 2auxo.int working vaccine stock; lane 1: p2auxo.HTI int plasmid; lane 2: WVS of BCG.HTI 2auxo.int ; lane 3: BCGwt; lane 4: BCG transformed with empty 2auxo.int plasmid; lane 5: water; lane 6: molecular weight marker. PCR for right integration site, attR ( E,F ) left integration site, attL in the BCG.HTI 2auxo.int WVS; lane 1 WVS of BCG.HTI 2auxo.int ; lane 2: BCGwt; lane 3: distilled water; lane 4: molecular weight marker; lane 5: positive control, BCG.HIVconsv1 2auxo.int Working Vaccine Stock (recombinant BCG expressing the HIVconsv1 immunogen [36,43]).…”
Section: Figurementioning
confidence: 99%
“…Data from ongoing clinical trials to study the efficacy of BCG vaccination in healthcare workers will be available soon and it will play a critical role in the development of rBCG vaccines against COVID-19. Unequivocally, BCG is a suitable vector for the expression of SARS-CoV-2 antigens as it possesses several beneficial properties such as, its inherent adjuvant properties and suitability for neonatal administration [61] . Trained immunity induced by rBCG along with SARS-CoV-2 specific immune response can induce robust protection against COVID-19 and excellent safety profile in humans, low cost production and thermal stability further enhances the possibility of its human use in a limited time frame compared to other candidates where time consuming safety trials and infrastructure are needed before the vaccines reach the end users.…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…2 nd -generation conserved-region immunogens aimed to induce T-cell responses specifically against the conserved regions of HIV-1 proteome were expressed in novel BCG-vectored vaccine candidates, BCG.HIVconsv1 2auxo.int and BCG.HIVconsv2 2auxo.int . These candidates were well tolerated in adult BALB/c mice and induced HIV-1-specific T cell responses in addition to improving the mycobacterial vaccine stability and immunogenicity 43 . Murine studies to highlight the host-mycobacterial interactions using rBCG demonstrated a greater antigen-specific response in splenocytes from granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-2 and IFNγ -secreting BCG vaccinated mice compared to mice injected with BCG lacking cytokines 44 .…”
Section: Mouse Model In Tb/hiv Vaccinesmentioning
confidence: 99%